IBEACON based mobile marketing system for shopping mall - Zhang, Tianli (2016)
Nowadays, there are drawbacks in the shopping mall management. Many markets do not provide satisfactory shopping services to customers. And, iBeacon technology and mobile technology are the great hot topics in the market. Due to the great business opportunities, a system whose goals are to improve the shopping behaviors and to enhance the retail management by using iBeacon technology is to be implemented. The system has the following functions: • iBeacon trigger event. • CRM: based on gender, age to push advertisement. • CMS: Outlet can upload advertisement even using mobile. • Database in cloud server. • Outlet staff can detect who is inside the outlet. In this thesis, the architecture of this system is introduced from physical layer, software layer and application layer. Then, the system design and implementation is introduced in detail. The tutorial writing style is chosen to explain the implementation including configuration of cloud server, database design and three mobile applications clearly.